The translator as cultural mediator in research publication - Bennett, Karen (2013)
Given the imbalance that exists between English and other languages in research publishing today, academic translators working into English are obliged to orient their translations towards Anglo-Saxon norms and values in order to ensure acceptance by international journals. However, when the norms governing textual production in the source culture are very different from those of the target culture, extensive domestication is required, which may be difficult for authors to accept. Hence, the translator needs a profound understanding of the values and assumptions underpinning the discourses in question in order to act as cultural mediator, sensitively negotiating the construction of a text that is acceptable to both parts.